On the importance of understanding older tourists: addressing the complexity of ageing travellers - Balderas-Cejudo, Adela (REVISTA QUAESTIO IURIS, 2022)
Abstract Ageing transcends age and goes beyond the older generations. Awareness of the way older individuals behave in tourism beyond clichés, labels and stereotypes and a clearer perspective of the economic benefits of the silver economy for companies in general and the tourism sector in particular is critical. Tourism providers, governments, and stakeholders in many developed countries of the world have identified older travellers as a priority market because of global demographic changes and the increased participation of older individuals in tourism and leisure activities. Despite the fact that the tourism industry is experiencing its most difficult period in history as a result of COVID-19, an increasingly healthy older individuals market segment with financial means to travel for leisure and a desire to visit new places holds enormous potential for cultural heritage and tourism. Methodology: In order to better understand the need and wants, some gaps in the literature have been identified in relation to the need to comprehend the requirements and expectations of an ageing population in order to have a better grasp of future tourism trends related to older travellers (Huang and Tsai 2003; Lehto et al. 2008), as well as the awareness of the potential economic value of the silver economy, which is less understood (McGuirk et al., 2021). In numerous ways, the increased demand for travel by older individuals presents a challenge for tourism professionals (Bakucz et al., 2021). Objectives: The aim of this article is twofold: to increase awareness and understanding of a yet misunderstood and undervalued market segment, beyond stereotypes and clichés and (2) to contribute to the tourism industry in terms of practical considerations. Findings: The findings regarding awareness and practical implications aid stakeholders in gaining a better understanding of older travellers and the need to meet the changing needs and expectations of an ageing population.